Health Technology Assessment of Drugs in Ireland: An Analysis of Timelines - Connolly, Emma (Pharmacoecon Open, 2019)
BACKGROUND: The National Centre for Pharmacoeconomics (NCPE) is commissioned by the Corporate Pharmaceutical Unit of the Health Service Executive (HSE-CPU) to assess the evidence for the comparative effectiveness and cost effectiveness of drugs for use by patients in Ireland. All new drugs are required to undergo rapid review (RR) appraisal by the NCPE. Following this, high-cost drugs or those predicted to have a significant budget impact then undergo a full health technology assessment (HTA) appraisal by the NCPE. OBJECTIVE: The objective of this paper was to quantify each stage of the timeline from marketing authorisation (MA) to completion of HTA appraisal and explore the association between submission features and the time to appraise RRs and HTAs. METHODS: All RRs and HTAs submitted to the NCPE (2015–2017 inclusive) were included in the dataset. Several dates and features of each submission were also listed for the purpose of analysis. RESULTS: A total of 158 RR and 49 HTA appraisals were completed by the NCPE between 2015 and 2017. The median time from MA to submission of RR was 59 days; the median time to appraise RR was 31.5 days. Only 49% of RRs appraised (2015–2017 inclusive) were recommended for HTA. The median time from RR decision to submission of HTA was 115 days, and the median time taken by the NCPE to appraise an HTA was 131 days. CONCLUSION: This paper identifies which stages of the process make a substantial contribution to the HTA timeline. Time to submission of RR varied widely between submissions, with only a few companies choosing to submit prior to an MA being granted. The average RR appraisal time was in line with the 4-week timeframe set out in a 2016 agreement. The time to appraise an HTA was longer than the 90-day timeframe.